Ore Deposit Models #12. The Platinum Group Element Deposits: Classification and Genesis - Macdonald, A. (Geoscience Canada, 1987)
Abstract The platinum group element deposits are sub-divided within a genetic framework; the threeprincipal deposit types are formed by(1) Orthomagmatic, (2) Alluvial or (3) Hydro-thermal processes. The Orthomagmatic classcan be further subdivided into three sub-classes: deposits that formed as a result of(a) magma mixing, (b) contamination ofmagma by material from an external source,and (c) deuteric fluid activity, i.e. flow of fluidsderived from the same magma as the intrusivehost rocks. Alluvial deposits include modem placers,which commonly show an association withmafic/ultramaflc complexes such as "Alas-kan-" or "Alpine-type" intrusions, andpaleoplacers, of which the Witwatersrand isthe only known example that is sufficientlyrich in the platinum group of elements topermit recovery. Hydrothermal platinum-palladium depositsinclude those in which a hydrothermal systemhas been channelled through mafic/ultra-maflc host rocks from which the preciousmetals may have been leached. Examplesinclude the New Rambler Mine in Wyoming,the Rathbun Lake occurrence in Ontario, andthe Nicholson No. 2 uranium ores in theBeaverlodge area of Saskatchewan. Thealkaline suite of porphyry copper depositscomprises the second type of hydrothermalmineralization in which platinum and pal·ladium are significantly concentrated. Thehuge Kupferschiefer Cu-Ag deposits in Cen-tral Europe contain locally significant con-centrations of platinum and palladium,associated with redox fronts in carbonaceousshales. At the Coronation Hill deposit, in Aus-tralia's Northern Territory. PGE are also spa-tially associated with carbonaceous material,and with uranium and gold mineralization.